TINJAUAN PERLINDUNGAN HUKUM TERHADAP PELANGGARAN HAK MORAL DALAM PEMUTARAN FILM DI BIOSKOP SEBAGAI KARYA CIPTA SINEMATOGRAFI OLEH PENGGUNA APLIKASI SOSIAL MEDIA INSTAGRAM (INSTASTORY) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Cinematographic are included in the protected copyright regulated in Undang-Undang Nomor 28 Tahun 2014. The definition of cinematographic in Undang-Undang Nomor 28 Tahun 2014 is creations with works that move both in the form of documentaries, advertisements, reportages or story films or a cartoon made with a screenplay. In recent years, the rise of film lovers who are also social media addicts often take pictures and record parts of films that are being screened in theaters and uploaded on social media accounts. When a part of the film is illegally recorded, moreover distributed, it is already in the category of piracy, and can be sued by the copyright holder if the copyright holder feels objections or feels disadvantaged over the act. The recording and dissemination occurred because of the very low public awareness about Copyright.The recording and dissemination action can give a "spoiler" which decreases the interest of the public to watch the film because they already know a part of the story of a film work so that it has an impact and has the potential to benefit the Creator and / or Copyright Holder from the film. The act of recording and distributing film footage in the instastory is also seen to violate the moral rights possessed by an Author and / or Copyright holder in the form of intentionally taking film footage distributed in the instastory without including the name of the Author who is obliged to pocket the permission of the owner if he wants to be distributed. The loss of economic rights and moral rights experienced by the creator and / or holder of this copyright can be the basis for a lawsuit for compensation to the perpetrators of acts of copyright infringement on films in theaters through social media.Keywords: Undang-Undang Nomor 28 Tahun 2014, cinematographic or films, distribution of films without permission, social media